Advancing the science of outcome measurement in paediatric palliative care. (2nd February 2019) - Harding, Richard; Chambers, Lizzie; Bluebond-Langner, Myra
Abstract : Background: There is a lack of appropriate, validated person-centred outcome measures (PCOM) for paediatric palliative care in the scientific literature, and as a result there is not a tool to drive and evaluate care of children and young people. Methods: In line with COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidance, an expert group was convened to elicit views on the domains/items to include in a PCOM, implementation challenges and requirements for use in routine care by practitioners. Data were content analysed. Results: 36 UK-wide clinicians, advocates, and researchers participated. 1) Items included were: specific symptoms, education, play and social interaction, parental time for partner and other children, sex and intimacy, and sibling wellbeing. 2) Implementation challenges: supporting children and young people to engage meaningfully, that the instrument could be seen as a 'test' of parents' care quality, raising unrealistic expectations, proxy validity. 3) There is a need for clear administration and interpretation guidance and for data ownership/access to be agreed. Conclusions: This expert meeting addressed the initial step in COSMIN guidance, informing face validity and acceptability. It provides the information necessary for the first phase of tool development and informs potential use and implementation.